COVID-19: Government Response and Community Participation Overcoming Outbreak and Managing its Impact - Hidayaturrahman, Mohammad; Yanti, Fitri; Husamah, H. (Universitas Islam Negeri Raden Intan Lampung, 2020)
Covid-19 outbreak has become a world pandemic, hundreds of countries in the world are stricken with the deadly virus. The average country in the world has the power to eradicate an outbreak that was first reported to appear in Wuhan, China. Countries in the world make efforts to handle it. This study aimed to (a) analyze the forms of government response in facing and dealing with the impacts caused by Covid-19, and (b) and analyzing the forms of community participation in the world to deal with effects of Covid-19. This research, which uses descriptive qualitative methods, collects data by searching online for various data sources (online media, journals, and scientific reports). From the research conducted, it was found that responsive governments tend to be able to control Covid-19. In addition, the great support of citizens to participate, became the second secret of faster handling of Covid-19.